2003
DOI: 10.1007/s10038-003-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

Two new mutations and three novel polymorphisms in the RB1 gene in Ecuadorian patients

Abstract: RB1 is the gene responsible for retinoblastoma, the most common malignant intraocular tumor of infancy and early childhood. There are no reports about this gene in Ecuadorian populations, and only a few studies have been published in Latin America about this subject. There is a spectrum of more than 370 mutations described in the RB1 gene mutation database (http://www.d-lohmann.de/ Rb/mutations.html), and alterations have been found in 25 of the 27 exons. During the exon-by-exon analysis of 31 tumor and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The hRAD54 , hMSH2 , ABCB1 , ABCC5 , COL18A1 , and SLC19A1 genes were consistent with lymphoma and leukemia in Latin Americans [153,154,155,156], as well as some Caucasians and Asians [157,158,159,160]. The RB1 gene was related with retinoblastoma in Latin Americans [161,162], and the TNFα and TP53 genes with cervical cancer [163,164,165,166,167,168]. …”
Section: Germline Cancer Predisposition In Latin Americamentioning
confidence: 99%
“…The hRAD54 , hMSH2 , ABCB1 , ABCC5 , COL18A1 , and SLC19A1 genes were consistent with lymphoma and leukemia in Latin Americans [153,154,155,156], as well as some Caucasians and Asians [157,158,159,160]. The RB1 gene was related with retinoblastoma in Latin Americans [161,162], and the TNFα and TP53 genes with cervical cancer [163,164,165,166,167,168]. …”
Section: Germline Cancer Predisposition In Latin Americamentioning
confidence: 99%
“…Rb is caused by mutations of the RB1 gene altering functional proteins, triggering cell division in the retina, and leading to the development of tumors [23]. According to , a previous study in Ecuadorians with Rb has described new mutations and SNPs [24]. For instance, a mutation found in exon 15 with a replacement of G to A (g.76920 G>A), and a mutation found in exon 22 with a replacement of T to C (g.IVS22-14 T>C).…”
Section: Discussionmentioning
confidence: 99%
“…Any form of radiation for investigation (like X-ray, CT scan) or treatment has to be preferably avoided in all germline cases, due to probable increased risk of second malignancies. Besides North America and Germany, RB1 mutations have been reported from various populations around the world like, Argentina (10), Brazil (11), China (12,13), Colombia (14), Ecuador (15), Egypt (16), India (17)(18)(19)(20)(21), Iran (22), Israel (23,24), Italy (25), Korea(26), Netherlands (27), Spain (28,29), Malaysia (30), Mexico(31), Morocco(32), New Zealand (33), Pakistan(34), Swiss (35), Tunisia(36) Singapore(37) Thailand (38) and United Kingdom (39). Out of ve earlier studies from India, stratifying genetic tests is an option suggested by Thirumalairaj et al (40).…”
Section: Read Full Licensementioning
confidence: 99%